Nanostructured Lipid Carriers for Improved Delivery of Therapeutics via the Oral Route - Alok Kumar Mahor; Prem Prakash Singh; Rishikesh Gupta; Peeyush Bhardwaj; Priyanka Rathore; Ankita Kishore; Rohit Goyal; Neeraj Sharma; Jyoti Verma; Jessica M. Rosenholm; Kuldeep K. Bansal (Journal of Nanotechnology)
Drug delivery via the oral route has always been challenging for poorly soluble drugs. Acid-induced hydrolysis, enzymatic degradation, and poor mucosal absorbency remain the primary hiccups for effective oral delivery of medications. With the advent of nanotechnology, nanostructured lipid carriers (NLCs) have emerged as a promising delivery carrier that can circumvent gastrointestinal tract (GIT) barriers hindering the solubility and bioavailability of such drugs. These NLCs can efficiently transport drug moieties across intestinal membranes shielding medications from intestinal pH and enzymatic degradation. Because they are composed of lipidic materials, they can be easily absorbed or taken up by various pathways such as transcellular absorption, paracellular transport, and M-cell uptake. Such mechanisms not only improve the absorption and solubility of drugs but also augment bioavailability and residence time and may bypass first-pass metabolism. This review explores the diverse applications of nanostructured lipid carriers (NLCs) in oral drug delivery for various medical conditions, shedding light on their current regulatory status, including FDA-approved options and those in pre/clinical stages. The review also features patented NLC formulations. It provides valuable insights into how NLCs can be harnessed for effective oral drug delivery and outlines recent advancements in optimizing their performance to tackle gastrointestinal barriers, thus opening new possibilities for NLCs in future pharmaceutical applications.